Improving critical thinking through problem-based learning with flipped classroom in pancasila education - Cici Purnamasari; Isnarmi Moeis; Suryanef Suryanef; Hasrul Hasrul (Journal of Educational and Learning Studies, 2026)
Objective: This study aimed to examine the effectiveness of integrating the Problem-Based Learning (PBL) model with Flipped Classroom principles in improving students' critical thinking skills in Pancasila Education. Methods: This study employed Classroom Action Research based on the Kemmis and McTaggart model involving 35 Grade XI students at SMAN 1 Tigo Nagari. The intervention was conducted over two action cycles comprising planning, action, observation, and reflection. Data were collected through observations, tests, interviews, questionnaires, and documentation, and analyzed using descriptive qualitative and quantitative techniques. Results: Students' critical thinking improved from 27.14% before the intervention to 54.05% in Cycle I and 80.00% in Cycle II. The mean learning achievement increased from 67.14 to 89.86, while classical mastery improved from 22.86% to 97.14%. Conclusion: Integrating PBL with Flipped Classroom principles effectively enhanced students' critical thinking skills and learning achievement by promoting active participation, collaborative inquiry, and meaningful learning experiences.